The impact of problem-based learning with argument mapping and online laboratory on scientific argumentation skill - Jumadi Jumadi; Riki Perdana; Riwayani Riwayani; Dadan Rosana (Institute of Advanced Engineering and Science, 2021)
Students in Indonesia still have the low level of scientific argumentation skills. This studypurposed to examine the impact ofProblem-based Learning (PBL) with Argument Mapping and Online Laboratory in improving the scientific argumentation skill. It describes the significance of the differences between participants who learn through PBL, PBL with Online Laboratory (PBL-OL), Problem-based Learning with Argument Mapping and Online Laboratory (PBL-AMOL) model. The population of this study were students from Madrasah Aliyah Negeri (MAN) Yogyakarta, Indonesia with a random sampling technique. This was quasi-experiment with pre and post test designs. In this study, there were 97 students at MAN 1 as respondent. Paired sample t-test, independent sample t-test and ANOVA mixed design was used to analysis data. The PBL-AMOL group has a significant difference based on pre-test and post-test (sig. 0000). The PBL-AMOL was most effective to improve the skill with gain score 0.43 (medium). Learning with the PBL-AMOL model can be an alternative to solve the problems of creative thinking skill.